Core-shell Fe3O4@Ag magnetic nanoparticles detection using spin-valve GMR sensing element in the wheatstone bridge circuit - Nur Aji Wibowo; Juharni Juharni; Taufikuddin Alfansuri; Lia Saptini Handriani; Harsojo Sabarman; Edi Suharyadi (Materials Research Express, 2020)
Core–shell Fe _3 O _4 @Ag magnetic nanoparticles (MNPs) integrated with a Wheatstone bridge-giant magnetoresistance (GMR) sensor provide access to GMR-based biosensors. The Fe _3 O _4 nanoparticles synthesized using the coprecipitation method demonstrated 77 emu g ^−1 of magnetization saturation ( M _S ), 51 Oe of coercivity ( H _C ), and particle size of 11 nm. Furthermore, core–shell Fe _3 O _4 @Ag MNPs prepared by the aqua-solution method possessed 53 emu g ^−1 of M _S , 145 Oe of H _C, and 17 nm of particle size. This high M _S of nanoparticles not only offer a large induced magnetic field but is sufficient for particle penetration within the biofilms. It was discovered that the sensor can distinguish between the bare Fe _3 O _4 with the Fe _3 O _4 @Ag nanoparticles through an output voltage increase corresponding to a decrease in M _S . The output signal of the sensor responds linearly to an increase in the core–shell Fe _3 O _4 @Ag nanoparticle concentration, owing to an increase in the induced-field. The sensor exhibits better sensitivity when applied in detecting less than 2 g L ^−1 of nanoparticle concentration, that is, 0.76 mV per unit of concentration (g/L).